Growth in euro area labour quality - Guido Schwerdt; Jarkko Turunen (European Central Bank (ECB), 2006)
Composition of the euro area workforce evolves over time and in response to changing labour market conditions. We construct an estimate of growth in euro area labour quality over the period 1983-2004 and show that labour quality has grown on average by 0.6% year-on-year over this time period. Labour quality growth was significantly higher in the early 1990s than in the 1980s. This strong increase was driven by an increase in the share of those with tertiary education and workers in prime age. Growth in labour quality moderated again towards the end of the 1990's, possibly reflecting the impact of robust employment growth resulting in the entry of workers with lower human capital. Labour quality growth has on average accounted for nearly one third of euro area labour productivity growth. The results point to a significant decline in the contribution of total factor productivity to euro area growth.
Keywords: E24; J24; O47; 330; growth accounting; Human capital; labour quality; total factor productivity; Humankapital; Arbeitsproduktivität; Produktivität; Wirtschaftswachstum; EU-Staaten